2013
DOI: 10.1002/mrd.22162
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signature to oxidative stress exposure at the time of embryonic genome activation in bovine blastocysts

Abstract: In order to understand how in vitro culture affects embryonic quality, we analyzed survival and global gene expression in bovine blastocysts after exposure to increased oxidative stress conditions. Two pro-oxidant agents, one that acts extracellularly by promoting reactive oxygen species (ROS) production (0.01 mM 2,2'-azobis (2-amidinopropane) dihydrochloride [AAPH]) or another that acts intracellularly by inhibiting glutathione synthesis (0.4 mM buthionine sulfoximine [BSO]) were added separately to in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 119 publications
1
26
0
Order By: Relevance
“…Interestingly, we found this later pathway upregulated in GH vs. ELC conceptuses (upregulation of PGD and TKT genes). The exposure of the zygote to high levels of glucose was associated with an increase in gene expression associated with oxidative stress (12,13). The fact that SLC2A1 is overexpressed in the EET of D18 conceptuses from heifers in our experiment could thus indicate a state of higher metabolic activity but also of higher oxidative stress.…”
Section: Metabolic Pathways Expressed In Conceptusesmentioning
confidence: 61%
“…Interestingly, we found this later pathway upregulated in GH vs. ELC conceptuses (upregulation of PGD and TKT genes). The exposure of the zygote to high levels of glucose was associated with an increase in gene expression associated with oxidative stress (12,13). The fact that SLC2A1 is overexpressed in the EET of D18 conceptuses from heifers in our experiment could thus indicate a state of higher metabolic activity but also of higher oxidative stress.…”
Section: Metabolic Pathways Expressed In Conceptusesmentioning
confidence: 61%
“…68 This study found that of the 231 gene changes in AAPH-treated blastocysts and 481 gene changes in BSO-treated blastocysts, 69 of the gene changes overlapped. This demonstrates that GSH-depletion causes many changes outside of traditional oxidative stress responses and may not induce many expected oxidative stress responses, as we have shown in this study.…”
Section: Discussionmentioning
confidence: 76%
“…Notwithstanding these limitations, the blastocyst is an interesting target to investigate. Transcriptome studies have extensively shown how early embryos interact with their immediate microenvironment [31, 57, 58]. Epigenetic reprogramming at this stage puts the embryo at risk of programming errors with potential long-term consequences due to an adverse environment [23].…”
Section: Discussionmentioning
confidence: 99%